Pengembangan Protatik (Program Tabel Fonetik) Berbasis Website sebagai Media Pembelajaran Pronunciation Practice - Retnomurti, Ayu Bandu; Octavita, RR Astri Indriana (citeus, 2017)
This research aims to develop manual modules into a versatile technology web-based module in Phonetic Table Program Protatik web-based and to explain the interest and the influence of the media in Pronunciation Practice class FBS Indraprasta PGRI University Jakarta. Verbal-based learning such as English pronunciation practice requires the existence of an effective media because if it is directly given without media, inaccuracies in pronunciation, spelling, repetition will occur. The research belongs to Research and Development that includes conducting of a preliminary study to examine the theory and supervise the product, developing and testing or validating a new product. Whereas the development requires an analysis, develops syllabus and materials, creates and revises media. As conducting the try out in the end of the lesson, students are required to give comments on Protatik concerning the advantages, disadvantages, suggestions for improvement the media. Protatik provides pronunciation models for students to practice and help them to understand the sound of English as it is equipped with buttons to practice presented by nonnative speakers.